Edukasi Pembuatan Linimen Fresh Oil dari Bahan Alami bagi Masyarakat Kelurahan Empus Kecamatan Bahorok. - Tambunan, Pravil Mistryanto; Saputri, Muharni; Rizki, Fanny; Ginting, Ernawaty (ABDIMASKU : Jurnal Pengabdian Masyarakat UTND, 2025)
Linimen Fresh Oil is a natural-based product with significant potential to support community health, particularly as a topical oil for pain relief and relaxation. This community service program aims to educate the residents of Empus Village, Bahorok District, on the production of Linimen Fresh Oil. The program is designed to enhance community knowledge and skills in utilizing local natural resources as raw materials for health products. The implementation methods include lectures, hands-on demonstrations, and intensive mentoring for participants. The ingredients used include coconut oil, essential oils such as peppermint and eucalyptus, and local herbal extracts readily available in the area. During the program, participants were taught simple yet effective formulation techniques, including blending, packaging, and storage procedures. Evaluation was conducted through pre-test and post-test surveys to measure participants' knowledge improvement and practical assessments to evaluate their skills. The results demonstrated a significant increase in participants’ understanding of the benefits and production techniques of Linimen Fresh Oil. Additionally, participants successfully produced the liniment independently, meeting quality standards for personal use and potential small-scale businesses. This program is expected to contribute to community self-reliance, local resource management, and economic well-being by developing natural-based products.